The Formation of Bivalents and the Control of Plant Meiotic Recombination - Gutiérrez Pinzón, Yared; González Kise, José Kenyi; Rueda, Patricia; Ronceret, Arnaud (Frontiers in Plant Science, 2021)
During the first meiotic division, the segregation of homologous chromosomes depends on the physical association of the recombined homologous DNA molecules. The physical tension due to the sites of crossing-overs (COs) is essential for the meiotic spindle to segregate the connected homologous chromosomes to the opposite poles of the cell. This equilibrated partition of homologous chromosomes allows the first meiotic reductional division. Thus, the segregation of homologous chromosomes is dependent on their recombination. In this review, we will detail the recent advances in the knowledge of the mechanisms of recombination and bivalent formation in plants. In plants, the absence of meiotic checkpoints allows observation of subsequent meiotic events in absence of meiotic recombination or defective meiotic chromosomal axis formation such as univalent formation instead of bivalents. Recent discoveries, mainly made in Arabidopsis, rice, and maize, have highlighted the link between the machinery of double-strand break (DSB) formation and elements of the chromosomal axis. We will also discuss the implications of what we know about the mechanisms regulating the number and spacing of COs (obligate CO, CO homeostasis, and interference) in model and crop plants.